Impulsivity influences betting under stress in laboratory gambling - Canale, Natale (Sci Rep, 2017)
Although recent research suggests that acute stress influences subsequent decision-making under ambiguity, less is known about the role of personality variables in this relationship. This study tested whether impulsivity traits and acute stress differentially influence the way in which a prior feedback is incorporated into further decisions involving ambiguity. Sixty college students (50% male; aged 18–25 years) were randomly assigned to a stress versus a non-stress condition before completing a laboratory gambling task. The results revealed that independently of the stress condition, subjects behaved as if the odds of winning increase after a single loss. Additionally, stress effects varied as a function of impulsivity traits. Individuals who lacked perseverance (i.e., had difficulty focusing on a difficult or boring task) gambled more after experiencing a loss in the stress condition than did those in the control condition. The present study supports that impulsivity traits can explain the differential effect of stress on the relationship between prior feedback and choices made under ambiguity.